Distal‐less homeobox 3, a negative regulator of myogenesis, is downregulated by microRNA‐133. Issue 2 (11th September 2018) - Qadir, Abdul S.; Lee, Jeeyong; Lee, Yun‐Sil; Woo, Kyung Mi; Ryoo, Hyun‐Mo; Baek, Jeong‐Hwa
Abstract: Distal‐less homeobox 3 (Dlx3), a member of the Dlx family of homeobox proteins, is a transcriptional activator of runt‐related transcription factor 2 (Runx2) during osteogenic differentiation. It has been demonstrated that forced expression of Runx2 induces an osteogenic program and ectopic calcification in muscles. Therefore, it would be reasonable to predict that Dlx3 also affects myogenic differentiation. The relationship between Dlx3 and myogenesis, however, remains poorly understood. Therefore, in this study, the role and regulation of Dlx3 during myogenic differentiation were investigated. Expression level of Dlx3 was downregulated in human mesenchymal stem cells (MSCs), mouse MSCs, and C2C12 cells cultured in myogenic medium. Dlx3 level was inversely correlated with myogenic differentiation 1 and the muscle‐specific microRNA, microRNA‐133 (miR‐133). The expression level of Runx2 was closely regulated by Dlx3 even under myogenic conditions. Overexpression of Dlx3 markedly downregulated expression levels of myogenic transcription factors and myotube formation in C2C12 cells, whereas Dlx3 knockdown enhanced myogenic differentiation. The Dlx3 3′‐untranslated region (3′‐UTR) has two potential binding sites for miR‐133. Luciferase reporter assays demonstrated that Dlx3 is a direct target of miR‐133a and miR‐133b, and that the two target sites are redundantly active. Taken together, these results suggest that Dlx3 is a negative regulator of myogenic differentiation and that miR‐133a and miR‐133b enhance myogenic differentiation, partly through inhibition of Dlx3 expression via direct targeting of the Dlx3 3′‐UTR. Abstract : Dlx3 is a negative regulator of myogenic differentiation. MiR‐133 enhances myogenic differentiation partly through inhibition of Dlx3 expression.